Experimental characterization of compaction wave propagation in cellular polymers. (15th May 2018) - Ravindran, Suraj; Koohbor, Behrad; Malchow, Peter; Kidane, Addis
Highlights: Elastic precursor velocity and compaction wave velocities are estimated from the full-field measurement. Spatial variation of inertia stress, particle velocity, acceleration field and compaction wave thickness are calculated from the particle displacement. Critical impact velocity to generate shock is estimated. Abstract: A great-deal of literature is available in the study of compaction wave propagation in cellular materials. However, experimental investigations concerning the spatial variation of the deformation features of compaction waves are limited. In this study, the formation and propagation of compaction wave in a low density polymeric foam under intermediate velocity projectile impact loading is investigated experimentally. The results are discussed in terms of the compaction wave characteristic parameters such as compaction wave velocity, axial strain, particle velocity, etc. In addition, spatial distribution of inertia stress during compaction wave propagation, and the critical velocity required to form shock are estimated. The stress jump across the compaction wave is also calculated using an inertia stress analysis and compared with the shock theory. It was observed that an elastic precursor propagates, at a velocity of 740 m/s, along the material upon impact, and it decays as it propagates along the specimen. Whereas, the compaction wave formed following the elastic precursor was propagated at a constant velocity much slower than the elastic precursor. Inertia stress calculations shows that the fast moving elastic precursor is reflected from the distal end and reduces the inertia component of the total stress. On the other hand, the compaction thickness is seen to be approximately constant during the entire duration of the compaction wave propagation after the achievement of the quasi-steady condition.